Headache and Nausea after Treatment with High‐Dose Subcutaneous versus Intravenous Immunoglobulin. Issue 6 (29th June 2015) - Markvardsen, Lars H.; Christiansen, Ingelise; Andersen, Henning; Jakobsen, Johannes
Abstract: Treatment with intravenous immunoglobulin (IVIG) leads to transient side effects such as headache and nausea during and after the infusion. We hypothesized that subcutaneous administration of smaller doses of immunoglobulin (SCIG) given more frequently leads to less severe headache and nausea and could be an alternative in patients experiencing side effects. Fifty‐nine patients diagnosed with neurological disorders (chronic inflammatory demyelinating polyneuropathy (CIDP), multi‐focal motor neuropathy (MMN) or post‐polio syndrome) were treated with IVIG, and 27 CIDP or MMN patients with SCIG. For two consecutive weeks daily, registration of the severity of headache and nausea was registered on a visual analogue scale (VAS) from 0 to 100 mm. In the SCIG group, headache reached a peak value of 1 (0–13) mm at day 6 versus 11 (0–96) mm in the IVIG group at day 4 ( p  < 0.0001). For nausea, the SCIG group had a stable value of 0 (0–21) mm at all days, whereas a peak value of 3 (0–90) mm was reached at day 4 in the IVIG group ( p  < 0.0001). SCIG leads to less severe headache and nausea than IVIG without fluctuations of side effects in relation to the injections.